2001
DOI: 10.1212/wnl.57.7.1222
|View full text |Cite
|
Sign up to set email alerts
|

Silent MRI infarcts and the risk of future stroke

Abstract: The presence of silent cerebral infarcts on MRI is an independent predictor of the risk of symptomatic stroke over a 4-year follow- up in older individuals without a clinical history of stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
238
0
18

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 340 publications
(267 citation statements)
references
References 23 publications
10
238
0
18
Order By: Relevance
“…Among CKD patients, the prevalence of silent infarcts is inversely reported to kidney function as measured by cystatin C in the Cardiovascular Health Study (38); among hemodialysis patients in another study, the prevalence was 49 percent, or 5 times more common than in control subjects (39). Silent strokes are associated with increased risk of subsequent clinically evident stroke, cognitive and physical decline, and incident dementia (36,37,40) in both the general and CKD/dialysis populations (39,41).…”
Section: Subclinical Cerebrovascular Disease: Silent Infarcts and Whimentioning
confidence: 99%
“…Among CKD patients, the prevalence of silent infarcts is inversely reported to kidney function as measured by cystatin C in the Cardiovascular Health Study (38); among hemodialysis patients in another study, the prevalence was 49 percent, or 5 times more common than in control subjects (39). Silent strokes are associated with increased risk of subsequent clinically evident stroke, cognitive and physical decline, and incident dementia (36,37,40) in both the general and CKD/dialysis populations (39,41).…”
Section: Subclinical Cerebrovascular Disease: Silent Infarcts and Whimentioning
confidence: 99%
“…Compared with symptomatic cardiovascular disorders such as stroke and coronary heart diseases, SCI and intracranial stenosis have been understudied in terms of their risks and consequences. Some studies showed SCI was associated with future stroke (14)(15)(16)(17)(18). However, the relationships among SCI, intracranial stenosis, carotid plaque, IMT, and baPWV are scarcely known.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of studies showed a relationship between dementia occurrence and volume or strategic location of infarction, a host of cranial CT and MRI [14]. These studies provide evidence that dementia related to stroke is associated with higher mean tissue loss, infarct number, location (eg, dominant thalamus and angular gyrus, bilateral infarcts, deep frontal infarcts, left hemisphere infarcts), and degree of "cerebral atrophy" as demonstated by ventricular size, area of subarachnoid space, and size of the third ventricle.…”
Section: Discussionmentioning
confidence: 99%